Building a Boot Camp: Pediatric Residency Preparatory Course Design Workshop and Tool Kit - Amanda Hartke; Erin Pete Devon; Rebekah Burns; Molly Rideout (Association of American Medical Colleges, 2019)
Introduction Although many medical schools are adding residency preparatory courses or boot camps to their curricula, there is little published guidance for faculty tasked with designing them. We developed a workshop and accompanying boot camp course design tool kit to assist faculty in creating a pediatric boot camp course following the initial steps of Kern's framework for curriculum development. Methods Learners participated in a 2-hour workshop incorporating short didactics, guided independent reflection, and group discussions. Workshop facilitators guided faculty through the tool kit materials including a literature overview, a needs assessment worksheet, session prioritization and schedule planning worksheets, a module design worksheet, and implementation strategies. Results Twenty-seven attendees at a national meeting of undergraduate pediatric educators participated in the workshop. Feedback was solicited via an anonymous electronic survey (41% completion rate), which indicated that attendees' self-assessed confidence significantly increased for each component of the tool kit. For the five tool kit components surveyed, average confidence increased 26% (range: 17.5%-37.1%) after completing the workshop. All respondents also indicated that the tool kit would be moderately helpful to very helpful as a stand-alone resource for independent faculty use, corresponding to a 3.57 out of 5 weighted average for this Likert-scale question. Discussion We developed a pediatric boot camp course design workshop and tool kit to assist faculty in developing pediatric boot camps. Initial implementation was through a workshop, but the resource could be used individually and also adapted for use by other specialties.